Pengaruh Pembelajaran Student Facilitator and Explaining terhadap Hasil Belajar IPS di Kelas VIII MTSN 1 Bener Meriah - Lia Itawari; Eka Susanti; Fatkhur Rohman (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
The purpose of this research is to find out: 1) To find out learning outcomes before using Student Facilitator And Explaining learning at MTsN 1 Bener Meriah. 2) To find out the learning results after using the Student Facilitator And Explaining learning at MTsN 1 Bener Meriah. 3) To find out whether there is a significant influence after using Student Facilitator And Explaining learning on social studies learning outcomes at MTsN Bener Meriah. The research used was quantitative research with an experimental method approach and the population and sample in this research were students at MTsN 1 Bener Meriah in class VIII-1 totaling 30 students and VIII-4 totaling 28 students. Based on the analysis of the data obtained: 1) the social studies learning results of class VIII MTsN 1 Bener Meriah students show an average score of 40.50, while in the control class the average score is 37.14. 2) The social studies learning results of class VIII MTsN 1 Bener Meriah students obtained an average score of 70.70. Have good learning outcomes. 3) through the results of hypothesis testing, the tcount was 9.457 and the Sig. (2-tailed) of 0.000 < 0.05, it can be concluded that there is a significant influence from Student Facilitator And Explaining learning on the learning outcomes of students in social studies subjects in class VIII MTsN 1 which are truly cheerful.